Getting the Advantage of Free Software to Generate Holistic Spelling Activities - Choiriya, Choiriya (Universitas PGRI Adi Buana Surabaya, 2016)
Teaching spelling could be frustrating and boring at thesame time for both teachers and students. It also has to be tailoredto meet the needs of the students. Ready-made materials may nothelp as easy. This workshop will give useful input on whichsoftware can be used and how to use it. You will also learn tomake a series of spelling activities good to meet the needs of yourstudents disregarding their age groups. Some of the suggestedsoftware is Word-Search Generator for worming up, Eclipsecrossword puzzle maker for meaning and Ant-Word-Profiler forproduction. Repletion is a very good method to use, each of thesoftware above stressing on different technique that helps thestudents getting accustomed with the English spelling of thetargeted language and also having fun doing it. The ideas of theseactivities are adapted from Nelson English Spelling Book but theyare limited to be used only by young age native speakers.